2014
DOI: 10.1159/000368401
|View full text |Cite
|
Sign up to set email alerts
|

Water and Electrolyte Disorders at Long-Term Post-Treatment Follow-Up in Paediatric Patients with Suprasellar Tumours Include Unexpected Persistent Cerebral Salt-Wasting Syndrome

Abstract: Background: Patients with brain tumours have a high risk of water and electrolyte disorders (WED). Postsurgery diabetes insipidus (DI) may be transient or permanent, the syndrome of inappropriate antidiuretic hormone secretion (SIADH) and cerebral salt-wasting syndrome (CSWS) are usually transient. Methods: Retrospective study, including patients with suprasellar tumours, treated at Hôpital Necker, Institut Gustave-Roussy or Institut Curie, in Île-de-France, between 2007 and 2011. WED were noted if they persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…This finding is in contrast to our speculations and previous reports, which suggest that damage to anterior and posterior hypophysis in craniopharyngioma management is more severe than in other surgical interventions causing ADI (1). Management of ADI is generally challenging, as the time of adipsia recovery is variable, and central DI persists despite adipsia recovery.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is in contrast to our speculations and previous reports, which suggest that damage to anterior and posterior hypophysis in craniopharyngioma management is more severe than in other surgical interventions causing ADI (1). Management of ADI is generally challenging, as the time of adipsia recovery is variable, and central DI persists despite adipsia recovery.…”
Section: Discussioncontrasting
confidence: 99%
“…The occurrence of diabetes insipidus (DI) following neurosurgical procedures for brain tumors may be transient or permanent (1). Adipsia rarely accompanies DI (ADI) due to osmoreceptor destruction.…”
Section: Introductionmentioning
confidence: 99%
“…disclosed that radical excision, recurrent tumor surgery, pituitary stalk injury, and transcranial approach are associated with higher incidence of postoperative DI, being in their series as high as 80%. They pointed out that fluid/electrolytes disorders, especially the so‐called “triphasic response” more commonly seen in children frequently leads to a differential diagnosis of DI vs SIADH . So, the immediate postoperative response of stalk/hypothalamus manipulation is temporary dysfunction with polyuria, followed by the antidiuretic phase due to the uncontrolled release of vasopressin from the posterior pituitary or the damaged hypothalamus; finally, another polyuric phase, when the ADH reserves are depleted.…”
Section: Intradural Tumorsmentioning
confidence: 99%
“…Although DI is usually a common complication in patients with craniopharyngioma presenting in 61% of patients, adipsic DI represents a more infrequent complication, in the review made by the authors, 20 patients were found who presented this pathology secondary to craniopharyngioma 16–24. No associations were found in the literature with a particular type of histopathological pattern.…”
Section: Discussionmentioning
confidence: 92%